2017
DOI: 10.5539/hes.v7n3p161
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Literature: Plagiarism in the Papers of Turkish Context

Abstract: The present review attempted to address the direction of plagiarism literature in Turkish context. 15 studies conducted in Turkey on plagiarism were analyzed through content analysis. The context, purposes, methodological issues and results of researching plagiarism were categorized. The findings of this review indicated that although plagiarism's raising legal and ethical concerns is acknowledged by Turkish researchers, there are limited numbers of studies exploring the plagiarism perceptions, views, situatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…The reason why the present study was conducted is because the issue of avoiding plagiarism has been a serious concern in the Turkish tertiary education context. One study that reviewed the methodology and results of the previous studies on plagiarism in the Turkish context acknowledges that the awareness of legal and ethical concerns has risen among Turkish researchers, but in the study it is stated that there is still a limited amount of research on students' perceptions of plagiarism (Gokmenoglu, 2017). Gokmenoglu refers to the most comprehensive plagiarism-related project conducted in Turkey by the team of Education Policy Research and Application Centre of one of the most prominent universities of Turkey by examining 470 master's theses and 130 doctoral dissertations published between 2007 and 2016 in Turkey.…”
Section: The Turkish Contextmentioning
confidence: 99%
“…The reason why the present study was conducted is because the issue of avoiding plagiarism has been a serious concern in the Turkish tertiary education context. One study that reviewed the methodology and results of the previous studies on plagiarism in the Turkish context acknowledges that the awareness of legal and ethical concerns has risen among Turkish researchers, but in the study it is stated that there is still a limited amount of research on students' perceptions of plagiarism (Gokmenoglu, 2017). Gokmenoglu refers to the most comprehensive plagiarism-related project conducted in Turkey by the team of Education Policy Research and Application Centre of one of the most prominent universities of Turkey by examining 470 master's theses and 130 doctoral dissertations published between 2007 and 2016 in Turkey.…”
Section: The Turkish Contextmentioning
confidence: 99%
“…Fanelli published a commentary on academic misconduct in Nature, and argued that misconduct should be referred as "biased reporting" of all sorts: Misconduct is "any omission or misrepresentation of the information necessary and sufficient to evaluate the validity and significance of research, at the level appropriate to the context in which the research is communicated." Gokmenoglu 4 attempted to address the trend of literature published on plagiarism in the Turkish context. The findings of this study revealed that although the legal and ethical concerns are recognised by the Turkish researchers, still there are few studies undertaken by the researchers about plagiarism.…”
Section: Introductionmentioning
confidence: 99%
“…Se han realizado también algunas revisiones sistemáticas de la literatura sobre este tema como la de Gokmenoglu (2017), Orim (2017) en el contexto nigeriano, la de Stonecypher y Willson (2014) en el ámbito de la enfermería y algunas menos específicas, pero más antiguas como la de Ercegovac y Richardson (2004) o la de McCabe et al (2001) quienes analizan 10 años de investigación en el tema hasta el año 2000.…”
unclassified